1997
DOI: 10.1093/carcin/18.7.1419
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced levels in neonatal rat liver of 7,8-dihydro-8-oxo-2'- deoxyguanosine (8-hydroxydeoxyguanosine), a major mutagenic oxidative DNA lesion

Abstract: The purpose of this study was to determine whether the level of 7,8-dihydro-8-oxo-2'-deoxyguanosine (8-hydroxy-2'-deoxyguanosine) (8-oxo-dG), a major mutagenic DNA oxidation product, is enhanced in newborn rat liver DNA as a consequence of oxidative stress incurred during the early postnatal period. 32P-postlabeling showed this adduct to increase approximately 2-fold from the 20th day of gestation (2 days before birth) to a peak level at 50-53 h after birth. Postnatal levels exceeded fetal levels at all time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 6 publications
1
16
1
Order By: Relevance
“…The data thus indicate that rats are indeed confronted with early-postnatal oxidative stress (Gunther et al, 1993;Krukowski and Smith, 1976;Yoshimura et al, 1988). The discrepancy between our findings and those of Randerath et al (1997) may be, at least partly, due to the differences in detection methods (they apply 32 P-postlabeling) and the possible presence of mitochondrial DNA contamination. Fraga et al (1990) reported aging-dependent increase of 8-OHdG in the liver, kidney and intestine, but not brain or testis, of male Fischer 344 rats from 1 to 24 months of age.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The data thus indicate that rats are indeed confronted with early-postnatal oxidative stress (Gunther et al, 1993;Krukowski and Smith, 1976;Yoshimura et al, 1988). The discrepancy between our findings and those of Randerath et al (1997) may be, at least partly, due to the differences in detection methods (they apply 32 P-postlabeling) and the possible presence of mitochondrial DNA contamination. Fraga et al (1990) reported aging-dependent increase of 8-OHdG in the liver, kidney and intestine, but not brain or testis, of male Fischer 344 rats from 1 to 24 months of age.…”
Section: Discussioncontrasting
confidence: 53%
“…With regard to the pre-and postnatal changes in 8-OHdG steady-state levels in rat organs, Randerath et al (1997) demonstrated liver increase within 1 hour after birth, a peak at the 53rd hour and decrease by the 100th hour in neonatal Fischer 344 rats. We could not detect any elevation of nuclear 8-OHdG levels in the assessed organs during the prenatal and postnatal/preweaning period up to 2 weeks of age using HPLC-ECD, with the single exception of a small increase in the liver at 7 days.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We speculate that the proposed alterations in mitochondrial function during hypoxia further enhance production of ROS upon reoxygenation, which might explain the current findings in hypoxic animals as opposed to controls. Furthermore, the sudden surge in partial oxygen pressure at birth has been reported to increase the amount of 8-oxoG in rat liver DNA (32), indicating a finely tuned equilibrium under physiological conditions. Mitochondrial dysfunction and defective translocation of OGG1, as seen with increasing oxidative stress in older mice (33), may cause disruption and a progressive accumulation of oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 95%
“…The rapid postnatal onset suggests that birth stress, which involves an increase in ROS levels (Randerath et al, 1997a;Randerath et al, 1997b) may trigger it and that rapid postnatal growth may further exacerbate it. Combined with the inability to repair certain endogenous lesions as in SIRT6 or NER deficiency, oxidative genotoxic stress may trigger an adaptive response intended to reduce generation of ROS through mitochondrial respiration and thus prevent further damage.…”
Section: Evolution Of the Preservative Stress Responsementioning
confidence: 99%